(untitled) (Research, Society and Development, 2021)
Introduction: The elderly population suffers from several changes due to senility, including xerostomia and hyposalivation. Objective: to carry out an integrative review in order to evaluate the different therapies described in the literature related to the treatment of xerostomia and hyposalivation in the elderly. Methodology: As a search strategy, an integrative bibliographic search was carried out in the electronic databases: PubMed, Lilacs and Web of Science, on the subject, using the following keywords: "Xerostomia", "Elderly", "Treatment" in association through the Boolean operator AND. Studies carried out only on humans between the years 2011 to 2021 were selected. Results: Among the 94 studies found, only 5 articles, published between the years 2011 to 2021, were used for the results. Conclusion: After analyzing the studies, it is possible to confirm the efficacy of several alternatives for the treatment of xerostomia and its scientific relevance and that xerostomia alone is not a disease, but non-treatment has serious dental implications, affecting oral health. and the patient’s general.